Molecular Cytogenetic Analyses and Sequencing in jute Corchorus species: An Amalgamation of Recent Advances and Research - Datta, Neelabh (International Journal of Scientific Research in Biological Sciences, 2022)
Genomic DNA (gDNA) from Corchorus olitorius O four was used for the High Throughput Next Generation Sequencing (NGS) podiums. About 50-fold coverage of Jute`s genome sequencing data was intended for the recombination assignment. Molecular analysis of repetitive DNA sequences, which account for a large percentage of plant genomes, has not been conducted in jute, but it may be useful for studying chromosome long-range organization. Several open-source and industrial-grade genome assemblage and annotation conduits were used for accumulating and appraise raw statistics. For authenticating the genome project, a transcriptome genome and proteome assessment were additionally also implemented for which evaluated data is assessed by exceptional computing resources, ranging from an overall high- performance cluster server to Dell servers, were used. The jute plant is well adapted to grow in hot and humid climates; however, it is typically grown in a wide range of climatic conditions. Abiotic stress can limit its growth, yield, and quality and affects the metabolism, growth, physiology, and fiber yield of the plant. Despite jute`s adaptedness to grow.in hot and humid climates, its growth can be adapted to a wide range of climates and it is relatively resistant to some environmental stresses. However, abiotic stress hinders both jute`s growth, yield, and quality significantly. Jute is restricted in its growth, yield, and quality significantly by abiotic stress. Abiotic stress directly affects jute`s metabolism, growth, physiology, and fiber yield. However, the utmost proficient array of 858 EST was deposited in the Gene Bank database. Ostensibly, the communal record is far from satisfactory to apprehend the molecular machinery of filamentous biosynthesis. In this review I will cite some of the recent information in the field of sequencing and analysis of Jute (Corchous species) plant by which we can develop jute varieties that are highly productive, saline-tolerant, and produce good quality fibre, including strength and color.